Assessment of Wood Traits Variation in the Segregating Populations of Eucalyptus hybrids - Verma, S. K.; Sharma, S. K. (Indian Forester, 2011)
The present paper reports the genetic variation observed in wood propertieS viz., fiber length, fiber diameter, lumen diameter and wall thickness in segregating populations of F2 reciprocal hybrid class (E. citriodora Ã— E. torelliana), F3 E. citriodora Ã— E. torelliana and parents (E. citriodora and E. torelliana) which were developed at New Forest Dehradun (India). A subtle range in variation in wood properties was observed due to segregation when compared with parents. The differences in wood properties of outer, middle and inner segments of core samples were found statisticaUy significant for increase in specific gravity. The individuals in F2 and F3 generations have recorded higher fibre length, outer fibers diameter and less wall thickneSs as compared to parents. The differences between parents and segregating populations were found significant. Significant negative correlations were found between outer fiber diameter and dbh, specific gravity and fiber length, fiber lumen diameter and dbh, specific gravity and fiber length while significant positive correlation was found between specific gravity and fiber wall thickness.